1997
DOI: 10.1038/sj.bjp.0701045
|View full text |Cite
|
Sign up to set email alerts
|

β‐Adrenoceptor‐mediated effects in rat cultured thymic epithelial cells

Abstract: Sympathetic nerves were visualized in sections from rat thymus by immunostaining of tyrosine hydroxylase, the rate‐limiting enzyme of catecholamine biosynthesis, and by glyoxylic acid‐induced fluorescence of catecholamines. Catecholaminergic nerve fibres were detected in close connection to thymic epithelial cells which therefore might be preferred target cells. To evaluate this, rat immunocytochemically defined, cultured thymic epithelial cells were investigated for adrenoceptors and adrenergic effects. In ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
6

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 25 publications
0
44
0
6
Order By: Relevance
“…Tracing analysis indicates that thymic sympathetic outflow directly starts in neurons from the thoracic spinal cord, brainstem, caudal raphe nucleus, and hypothalamus (Trotter et al, 2007). Furthermore, the neurotransmitter norepinephrine (Singh and Owen, 1976;Felten et al, 1987;Morale et al, 1992;Tsao et al, 1996;Kurz et al, 1997;von Patay et al, 1998von Patay et al, , 1999 is found in the thymus, and thymic cells express both ␤1-and ␤2-adrenergic receptors (Morale et al, 1992;Kurz et al, 1997;von Patay et al 1999) able to modulate maturation of T precursor cells and influence the thymic microenvironment. Thus, a link between the brain and the thymus is supported at different levels.…”
Section: Autonomic Denervation Of the Gld Thymusmentioning
confidence: 99%
“…Tracing analysis indicates that thymic sympathetic outflow directly starts in neurons from the thoracic spinal cord, brainstem, caudal raphe nucleus, and hypothalamus (Trotter et al, 2007). Furthermore, the neurotransmitter norepinephrine (Singh and Owen, 1976;Felten et al, 1987;Morale et al, 1992;Tsao et al, 1996;Kurz et al, 1997;von Patay et al, 1998von Patay et al, , 1999 is found in the thymus, and thymic cells express both ␤1-and ␤2-adrenergic receptors (Morale et al, 1992;Kurz et al, 1997;von Patay et al 1999) able to modulate maturation of T precursor cells and influence the thymic microenvironment. Thus, a link between the brain and the thymus is supported at different levels.…”
Section: Autonomic Denervation Of the Gld Thymusmentioning
confidence: 99%
“…The thymus of young adult animals is richly innervated by the SNS [29][30][31][32][33][34][35][36][37][38]. Thymic NA nerves originate primarily from the superior cervical and stellate ganglia [30,39,40].…”
Section: Sympathetic Neurotransmission In the Thymusmentioning
confidence: 99%
“…As mudanças no tamanho do timo quando da puberdade podem estar correlacionados com as alterações hormonais (Vizi et al 1995, Olsen & Kovacs 1996, Kurz et al 1997), e estes achados corroboram com a hipótese de Marchetti et al (1990) os quais relataram que o sistema nervoso simpá-tico está envolvido com a resposta da célula tímica à ação hormonal por mudanças de receptores dentro da glândula, confirmando assim nossos achados os quais indicaram variação de tamanho das células em relação à idade. E devido aos hormônios esteroides sexuais influenciarem na expressão de receptores nos timócitos houve a observação de diferença de tamanho entre machos e fêmeas no presente trabalho.…”
Section: Discussionunclassified